Використання проективної методики Вартегга в експрес-діагностиці курсантів-першокурсників - Доценко, В. В.; Dotsenko, V. V.; Вікторія Доценко (Вісник Національного університету оборони України. - 2014. - Вип. 3(40). - С. 212-216, 2014)
У статті представлені результати теоретичному аналізу та емпіричного дослідження можливостей використання тесту Е. Вартегга у психодіагностиці курсантів першого курсу. Визначено, що проективна методика незакінчених малюнків Е. Вартегга дозволяє швидко та інформативно дослідити ті глибинні, індивідуальні особливості курсантів-першокурсників, які найменше доступні безпосередньому спостереженню чи опитуванню за допомогою традиційних методів психодіагностики.

The results of theoretical analysis and empirical study of the possibilities of using the test E. Vartehha in psyhodiagnostics is shown in the article. There are determined that the projective technique unfinished drawings E. Vartehha allows quick and informative to explore the in-depth, individual characteristics of firstyear cadets who are least accessible to direct observation or survey using traditional methods of psychodiagnostics. Stated that most freshmen are actively searching their personal, unique way "I" focused, tend to be significant for the surrounding society, to express themselves and expand their influence. At the same time, some freshmen show a sense of uncertainty about the future and the desire to escape the past, anxiety and isolation, the deliberate understatement of the level of aspiration and ambition and complexity to overcome difficulties. Detected by the projection of subjective perceptions of personal meaning and meaningful experiences of first-year cadets will allow more elaborate directions and methods of psychological support students on stage to adapt to new training and performance.

В статье представлены результаты теоретического анализаи эмпирического исследования возможностей использования теста Э. Вартегга в психодиагностике курсантов первого курса. Определено, что проективная методика незаконченных рисунков Э. Вартегга позволяет быстро и информативно исследовать те глубинные, индивидуальные особенности курсантов - первокурсников, которые меньше доступны непосредственному наблюдению или опросу с помощью традиционных методов психодиагностики.
Usability of Vartehha`s projective techniq in rapid diagnostic of first-year cadets
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; проективні методи діагностики; психологічна діагностика; тест Е. Вартегга; курсанти першого курсу; projective techniques diagnostic; test E. Vartehha; курсанти; cadets; проективные методы диагностики; психологическая диагностика; тест Э. Вартегга; курсанты